A Qualitative Case Study on the Challenges of Acs Wasc Accreditation Preparation in King Mongkut’s International Demonstration School - Supsin, Thanakrit; González, Orlando Rafael González (Scholar: Human Sciences, 2020)
The aim of this research study was to identify the challenges of King Mongkut’s International Demonstration School (KMIDS) on the Accrediting Commission for Schools, Western Association of Schools and Colleges (ACS WASC) accreditation preparation, from the perspective of school administrators, school supervisor, ACS WASC coordinators and teachers. For this purpose, the researchers built and implemented an in-depth, structured interview protocol, which was conducted one-on-one with 17 participants. Member-checking and triangulation techniques were used in combination with notes from the observations and document reviews in order to ensure internal validity. The researchers applied a systematic qualitative design, consisting of open coding, axial coding, and selective coding, to analyze and interpret the collected data. Such inductive and deductive qualitative process led to the identification of 14 themes and 24 sub-themes oriented around the six categories of ACS WASC initial visit framework. Regarding “Organization for student learning”, there were four main challenges and eight sub-challenges found. Regarding “Curriculum, instruction and assessment”, there were two main challenges and six subchallenges found. Regarding “Support for student personal and academic growth”, there were two main challenges and two sub-challenges found. Regarding “Resource management and development”, there were one challenge and two sub-challenges found. Regarding “ONESQA standards for Thai language and Thai studies”, there were two main challenges and two sub-challenges found. Regarding “Boarding program”, there were three challenges found. Finally, recommendations for different stakeholders in relation to the six categories of ACS WASC initial visit framework, as well as for future researchers, are presented.